Penerapan Model Pembelajaran Blended Learning Dalam Meningkatkan Hasil Belajar Siswa Kelas VII Pada Mata Pelajaran IPS Terpadu di SMPK Nirmala Jopu - Yovita Gaa; Marsel Nande (Ekspektasi: Jurnal Pendidikan Ekonomi, 2024)
The background of this research is because teachers who always apply conventional learning models during learning so that it has an impact on student learning outcomes. The purpose of this study was to determine (1) The application of the blended learning model in class VII at SMPK Nirmala Jopu; (2) The learning outcomes of class VII students at SMPK Nirmala Jopu in social studies subjects after applying the blended learning model. The research method used is classroom action research (PTK). Data collection techniques are carried out through observation, tests, and documentation. The results of the study showed that the observation of teacher activities in the application of the blended learning model in cycle I was 75 percent including the "Good" category and increased in cycle II by 94.64 percent with the "Very Good" category, the results of the observation of teacher activities are in line with student learning outcomes. In the pre-cycle it was 65.45 percent, after the blended learning model was applied by utilizing the quizizz application in cycle I it increased to 66.66 percent and in cycle II it also increased to 85 percent. Thus, the proposed action hypothesis that the application of the blended learning model can improve student learning outcomes in the subject of social studies for class VII at SMPK Nirmala Jopu is declared accepted.